Bewegingen rond de huwelijkssluiting - Michels, Tĳs (Jaarboek voor liturgieonderzoek, 2001)
The article presents some findings of a recent survey of the form and perception of the rituals surrounding marriage. These rituals, and the ways in which they are looked upon, are changing fast. Thus, a ritual setting has developed which is significantly different from the one that dominated the Netherlands until quite recently, and far more diverse. To trace these developments, questions have been presented to couples that got married around 1963, as well as to couples that got married in 1997. The questions pertained to (1) rituals preluding to the wedding, like the proposal, (2) the civil ceremony, and (3) the church service, if any. Among the changes discussed are: a partial shift from a ‘rite of passage’ to a ‘rite of confirmation/finalization’; a shift from ‘public’ to ‘private’; a decrease in the responsiveness to religious interpretations; an increase in the time and effort invested in preparations; an increase in the endeavour to render the rituals less ‘impersonal’; a shift in the impression couples want their rites to convey, from ‘traditional’ to ‘original’; a rise in the appreciation and emotional impact of the civil ceremony; a shift in the civil ceremony, from ‘matter-of-fact’ to ‘stately’; a shift in the church service, from ‘social tradition’ to ‘decorative intimacy’; an increase in the festive nature of the day as a whole.